Atlas de la grande Europe - Beckouche, Pierre,Richard, Yann,Schulz, Martin (Autrement, 2013)
Includes bibliographical references
Keywords: Atlas; Mitgliedsstaaten; Regionalisierung; Globalisierung; Wirtschaftswachstum; Internationale Kooperation; Kultur; Wert; Norm; Kulturstandard; Geopolitik